2011
DOI: 10.1002/eet.567
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating and Regulating the Impacts of Lobbying in theEU? The Case Study of Green Industries

Abstract: How should we evaluate and regulate the impacts of lobbying in the European Union (EU)? The current lack of transparency around lobbying activities and the absence of formal regulation mean that a hidden lobbying problem may prevail. The tentative case study of green industries in the EU is illustrative. The wind turbine industry, for example, benefits from ambitious environmental target levels for greenhouse gas reductions that will increase the future market for renewable energy. In contrast, for example, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
(14 reference statements)
1
16
0
Order By: Relevance
“…This question has not been dealt with adequately in the literature, first and foremost because corruption is difficult to measure due to lack of regulation and transparency (Europa 2011). This is in stark contrast to the US experience, with its comprehensive and transparent legislation on corruption (Svendsen 2011).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…This question has not been dealt with adequately in the literature, first and foremost because corruption is difficult to measure due to lack of regulation and transparency (Europa 2011). This is in stark contrast to the US experience, with its comprehensive and transparent legislation on corruption (Svendsen 2011).…”
mentioning
confidence: 64%
“…In the case of legal rent-seeking, lobbyists can meet and try to influence political decision makers, e.g., informing decision makers about the consequences of smoking tobacco or liberalizing the agricultural sector in the EU. In addition to professional meetings, legal lobbying activities may include reports or publicity campaigns (Kurrild-Klitgaard 1998;Svendsen 2011).…”
Section: Bureaucratic Corruptionmentioning
confidence: 99%
“…This is a strong indication that the Chinese government wishes to promote Chinese industrial interests, at the same time protecting the public health. Also, wind turbine producers tend to be well-organized due to small-group advantages and one clear and common goal, namely to increase the megawatt production based on wind turbines (Svendsen, 2011).…”
Section: Coalition Formationmentioning
confidence: 99%
“…Although lobbying effectiveness is very difficult to measure due to its concealed nature in the process of decision-making (Lowery, 2002;Svendsen, 2011) and the great variety of ways the lobbying takes place (Lowery et al, 2008;Van Schendelen, 2012), it has empirically been shown that it does have an effect on the outcome of a lobbied concept (e.g. Baron & Hirsch, 2012;Gawande, Krishna, & Robbins, 2006;Gawande, Maloney, & Montes-Rojas, 2009;Husted, 1991;Kee, Olarreaga, & Silva, 2007;Panke, 2012;Vining et al, 2005).…”
Section: Lobbyingmentioning
confidence: 99%
“…Baron & Hirsch, 2012;Gawande, Krishna, & Robbins, 2006;Gawande, Maloney, & Montes-Rojas, 2009;Husted, 1991;Kee, Olarreaga, & Silva, 2007;Panke, 2012;Vining et al, 2005). Lobbying plays an important role as it can shape the decisions that are taken, make sure that a status quo prevails and influence the attitudes of decision-makers by moulding the political agenda (Baron & Hirsch, 2012;Gawande et al, 2009;Hojnacki & Kimball, 1998;Svendsen, 2011). The pursuit of economic benefits is usually the reason for lobbying (Crosby & Orsini, 1996;Mack, 2005).…”
Section: Lobbyingmentioning
confidence: 99%